Removal of Cobalt from Aqueous Solutions using Haro River Sand - Syed Moosa Hasany; Munawar Hussain Chaudhary (Adsorption Science & Technology)
The sorption of cobalt on Haro river sand has been optimized with respect to shaking time, amount of sand and concentration of cobalt. Maximum sorption (>94%) was achieved from deionized water at a v/w ratio of 90 cm3/g. Among the ions tested, EDTA, citrate, thiosulphate, tartrate, Pb II , Zn II , Cr III , Al III , Cd II and Mn II reduced the sorption significantly. Manganese(II), Zn II , Se IV , Cr III and Hl IV showed low sorption affinity towards the sand whereas Sc III , Au III and Zr IV were strongly sorbed. Cobalt, along with elements having higher sorption, could be separated from metal ions showing low sorption. The sand could be used for the preconcentration and removal of cobalt from aqueous solutions. The sand may be exploited for wastewater treatment and water pollution abatement. The sorption data followed the Freundlich adsorption isotherm. The characteristic parameters 1/n = 0.81 ± 0.03 and A = 14.2 ± 0.5 mmol/g were evaluated for the system.